PENERAPAN REALITAS TERPERKUAT (AR) UNTUK MENINGKATKAN KETERAMPILAN MOTORIK DAN MOTIVASI BELAJAR SISWA DALAM PENDIDIKAN JASMANI - Tegar Sukmawana; Nuryadi Nuryadi; Sucipto Sucipto (Tadulako Journal Sport Sciences And Physical Education, 2026)
This research was motivated by the existing phenomenon concerning the increasing demand for new media in physical education learning, especially in a digital age where physical activity needs have changed and interactive with adaptive approaches to increase participants psychomotor skills driven by education. This study aimed atsee the effectiveness of Augmented Reality (AR) technology in the learning of physical education to improve psychomotor ability, students with educational drive junior high school. Methods: The design was quasi-experimental with a pretest-posttest control group. The sample were 64 students from SMP Negeri 22 Bandung based on cluster random sampling into experimental with control groups. The intervention period was 8 weeks. Research instruments consisted of the Motor Skill Test and the Sport Motivation Scale II for Physical Education (SMS-II-PE) meeting validity with reliability standards. Overall, the experimental group had a significant higher increase in psychomotor mastery than controls (32.3% vs 12.3%; p < 0.05; Cohen’s d = 0.84). Additionally, the educational drive of experimental group speih ↑ 87% in thictixs of intrinsic motivation for understanding, countrline perception, with engagement during learning (p<0.05). These results suggest that motor learning processes can be strengthened and active student participation increased through interactive learning experiences, visual movement simulations, and direct AR feedback. Because of this, augmented reality technology has been shown to be a successful teaching tool for enhancing junior high school students' psychomotor skills and motivation in physical education classes.